2021
DOI: 10.3390/foods10112565
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Calcium-Binding Site, Absorption Activities, and Thermal Stability of Egg White Peptide–Calcium Chelate

Abstract: With the current study, we aimed to determine the characteristics and calcium absorption capacity of egg white peptide–calcium complex (EWP-Ca) and determine the effect of sterilization on EWP-Ca to study the possibility of EWP-Ca as a new potential calcium supplement. The results of SEM and EDS showed a high calcium chelating ability between EWP and calcium, and the structure of EWP-Ca was clustered spherical particles due its combination with calcium. The FTIR and Raman spectrum results showed that EWP could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Moreover, a bridging effect was formed by the combination of amino and carboxyl groups in the peptide with calcium, which can also change surface properties [ 33 ]. This phenomenon is similar to cases of egg white peptide–calcium chelate [ 37 ] and chicken foot broth byproduct peptide–calcium chelate [ 10 ], which shows that chelation with calcium ions results in a more compact, granular, and crystal-like structure.…”
Section: Resultssupporting
confidence: 76%
“…Moreover, a bridging effect was formed by the combination of amino and carboxyl groups in the peptide with calcium, which can also change surface properties [ 33 ]. This phenomenon is similar to cases of egg white peptide–calcium chelate [ 37 ] and chicken foot broth byproduct peptide–calcium chelate [ 10 ], which shows that chelation with calcium ions results in a more compact, granular, and crystal-like structure.…”
Section: Resultssupporting
confidence: 76%
“…Liu et al (26) suggested that wheat germ protein-derived calcium-binding peptides are rich in Glu, Asp, and Arg. Bao et al (27) pointed out that the calcium-binding site of polypeptide might be carboxyl groups of Asp and Glu. Consequently, both the Asp and Glu residues in the SPP might contribute to chelation with calcium ions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the molecular weight of SPP was 750.65 Da determined by LC-MS, as shown in the Supplementary Figure 1, supporting prior research that the peptide with low molecular weight demonstrates an enhanced affinity to calcium (24,25). The high proportion of acidic amino acids in SPP also has been reported to contribute to calcium chelation (26,27). Therefore, SPP could act as an effective carrier in delivering calcium.…”
Section: Molecular Dynamic Simulation Of Spp-camentioning
confidence: 99%
“…The everted rat intestinal sac absorption model, used in studies of nutrient absorption effects, was used to measure the absorption of calcium krill peptide chelates (QEELISK-Ca) in a study by Sun et al The results showed that the absorption of QEELISK-Ca in the duodenum and the ileum was significantly higher than that of CaCl 2 , thus demonstrating that QEELISK-Ca had better absorption compared with inorganic calcium salts [ 60 ]. Similarly, the absorption of calcium egg white peptides chelates from was 32.38 µg/mL, which was significantly higher than that of CaCl 2 [ 96 ].…”
Section: Bioavailability Of Calcium–peptide Chelatesmentioning
confidence: 99%